(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper explores the interconnection between sustainable development (SD) and corporate social responsibility (CSR) through a critical legal lens. CSR has evolved from philanthropic acts of business houses to legally recognized obligations embedded within corporate governance. At the international level, frameworks such as the UN Global Compact, OECD Guidelines, and EU directives highlight the increasing alignment of CSR with sustainable development goals (SDGs). The study reviews the historical trajectory of CSR, examines its role in India’s developmental agenda, and analyses the legal and regulatory challenges in embedding CSR as a sustainable development tool. The paper concludes that while CSR laws have strengthened corporate accountability, inconsistencies in enforcement, reporting, and transparency remain critical hurdles that require reform and harmonization at both national and global levels.